Cultural Diffusion and The Unification Policies of Alexander the Great (2014)
Ancient and modern scholars have discussed Alexander the Great’s prowess and intelligence even as a great leader and conqueror who stood out among his contemporaries. This paper is designed to examine Alexander’s strategy in the process of administering his conquered territories. The argument being put forth here is that, while being a conqueror of nations and people, Alexander adopted stratagems to run a successful empire. The adoption of cultural diffusion was one of the strategics. Another was adopting unification policies that aided his governance of his empire. Alexander did not stop at being a mere conqueror, but his desire to unite the world seemed stronger than conquests which appeared paramount. Being properly educated and learned, lie realized that the beauty and uniqueness of the culture of his subdued subjects in various territories were not to be discarded into the waste bin of history where it may be difficult or impossible to retrieve. These strategics arc pointers to efforts of an effectual leader as enduring and vibrant as Alexander, who desired the amalgamation and prosperity of his known world. Further studies may examine the sustainability of this cultural diffusion and his unification ideology among his Diadochi.